Exploring intersectional variations in sexual pleasure, sexual autonomy, and important correlates - Alarcão, V.; Stefanovska-Petkovska, M.; Candeias, P.; Pascoal, P. M. (Social Sciences, 2022)
Research suggests that pressure to meet gender norms can limit social behaviors and ultimately promote poor health outcomes, such as disparities in decreased sexual pleasure, which are considered a central component of human rights and well-being. Previous studies have shown that sexual pleasure and sexual autonomy are gender-related, but little is known about these indicators in diverse populations. This study used data from a probabilistic sample of Cape Verdean immigrant (n = 127) and Portuguese native (n = 133) women and men who were in an intimate relationship enrolled in the FEMINA (Fertility, Migration and Acculturation) project to explore intersectional variations in sexual pleasure, sexual satisfaction, and distress considering their interplay with sexual autonomy and social representations regarding sexuality. For all participants and especially among men, sex is a very important part of life. Sexual autonomy was positively associated with sexual pleasure among Cape Verdean and Portuguese women and Portuguese men. Sexual distress was negatively associated with sexual pleasure among women, especially Cape Verdean women who reported higher sexual distress. This small-scale study is an example of an intersectional approach to sexual health and rights.